1999
DOI: 10.1117/12.372954
|View full text |Cite
|
Sign up to set email alerts
|

<title>Structurally embedded fiber Bragg gratings: civil engineering applications</title>

Abstract: In civil engineering it is of interest to monitor long-term performance of structures made of new lightweight materials like glass or carbon fiber reinforced polymers (GFRP I CFRP). In contrast to surface applied optical fiber sensors, embedded sensors are expected to be better protected against rough handling and harsh environmental conditions. We report on two recently done fiber optical sensor applications in civil engineering. Both include structurally embedded fiber Bragg grating (BG) arrays but have diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…iK-n;-= ,which is thermal-optical tensor and thermal expansion coefficient respectively , we obtain = (a + )dT = KT dT (8) 1 n Where K7 is thermal sensitivity. If strain not taken into account, (8) is the equation between FBG wavelength shift and temperature.…”
Section: Temperature Sensing Property Of Optical Fbgmentioning
confidence: 99%
See 2 more Smart Citations
“…iK-n;-= ,which is thermal-optical tensor and thermal expansion coefficient respectively , we obtain = (a + )dT = KT dT (8) 1 n Where K7 is thermal sensitivity. If strain not taken into account, (8) is the equation between FBG wavelength shift and temperature.…”
Section: Temperature Sensing Property Of Optical Fbgmentioning
confidence: 99%
“…iK-n;-= ,which is thermal-optical tensor and thermal expansion coefficient respectively , we obtain = (a + )dT = KT dT (8) 1 n Where K7 is thermal sensitivity. If strain not taken into account, (8) is the equation between FBG wavelength shift and temperature. If the optical fiber core is silicon dioxide,related a + In is about 6.67 x 1 O6Y>k' , the temperature sensitivity coefficient is about 1Opm/'5 for the FBG whose wavelength is also 1550nm.However, for different FBG fabricated process, the strain and temperature sensitivity coefficients ofFBG should be determined through experiments.…”
Section: Temperature Sensing Property Of Optical Fbgmentioning
confidence: 99%
See 1 more Smart Citation
“…The tensile tests indicated that the embedded FBG sensors were able to survive a high strain of 1.5%. The GFRP rock bolts equipped with FBG sensors were installed in a tunnel near Sargans, Switzerland for long-term load monitoring [ 42 , 43 ]. The installation scheme of the FBG-equipped GFRP rock bolts in a tunnel and the one year measurements are shown in Figure 9 .…”
Section: Rock Bolt Monitoring Using Smart Sensorsmentioning
confidence: 99%
“…The research on the penetration mechanism of jacked pile in viscous soil foundation is relatively small, and while its penetration mechanism is affected by many factors, it is difficult to find an effective research method. In recent years, many domestic and foreign scholars have examined temperature compensation technology, packaging technology, installation technology, and engineering applications of FBG sensors: Nellen et al [9] first measured the strain attenuation in a cable anchorage head during cable loading and operation using embedding sensors, conducted mechanical and thermal load tests, and calibrated the temperature and strain sensitivity. The reliability of wavelength shift caused by stress transfer, optical fiber mechanical failure, and thermal FBG decay was introduced.…”
Section: Introductionmentioning
confidence: 99%